Integrated Nutrient Management on Growth, Yield, Nutrient Uptake and Fertility Balance in Soybean (Glycine max L.) – Wheat (Triticum aestivum L.) Cropping Sequence - Singh, Narendra; Kushwaha, H. S.; Singh, Aditya (International Journal of Bio-resource and Stress Management, 2020)
A field experiment was conducted at Krishi Vigyan Kendra, Chitrakoot, Uttar Pradesh state, India to assess the effect of Integrated Nutrient Management on Soybean [(Glycine max (L.) Merrill] – Wheat (Triticum aestivum) for productivity, nutrient uptake and fertility balance during 2008-09 and 2009-10. 18 treatment included use of 50, 75, 100% NPK to soybean and wheat with combination of FYM, Vermicompost and cow pat pit (CPP) were tested. All growth parameters were recorded significantly higher with the application of 100% NPK through fertilizer+5 t ha-1 FYM during 2008-09 and 2009-10. Pooled Seed yield (2.52 t ha-1), straw yield (2.54 t ha-1), nutrient uptake (216.35 kg N, 34.70 kg P and 89.50 K kg ha-1) of soybean were also found significantly higher with the same application. The growth parameters of wheat have been found significantly higher with 100% NPK to wheat+residual effect of 50% NPK and FYM @ 10 t ha-1 in the kharif crop during two years. Pooled Seed yield (4.95 t ha-1), straw yield (4.99 t ha-1) and harvest index (49.75 %) of wheat were also obtained highest with same treatment combination during experiment. The soil nutrient status after harvest of second year wheat crop, the available N, P and K in soil were analyzed significantly higher under 100% NPK with residual effect of FYM @ 10 t ha-1 + 50% NPK over rest of the treatments.